2017
DOI: 10.1039/c6cc08746a
|View full text |Cite
|
Sign up to set email alerts
|

From 2-methylimidazole to 1,2,3-triazole: a topological transformation of ZIF-8 and ZIF-67 by post-synthetic modification

Abstract: Bridging ligand replacement in zeolitic imidazolate frameworks, ZIF-8 and ZIF-67, by 1,2,3-triazole was investigated. A complete substitution of 2-methylimidazole by 1,2,3-triazole resulted in a topological transformation of the parent framework from a sodalite (SOD) network to a diamond (DIA) network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
3
54
2
1
Order By: Relevance
“…SALE has been reported to drastically affect both the stability and the adsorption properties of the resulting frameworks . For instance, the Sen group has recently investigated the SALE of ZIF‐8 and ZIF‐67 with 1,2,3‐triazole and found that after the SALE reaction, the 2‐methylimidazole ligand was completely substituted with 1,2,3‐triazole, which resulted in the transformation of the topological transformation of the parent framework from an SOD network to a diamond (DIA) network . The resulting MOFs, Co‐triazolate (MET‐4) and Zn‐triazolate (MET‐6) were stable up to 250 °C, but they were less thermally stable than the parent ZIF‐67 and ZIF‐8, respectively.…”
Section: Strategies For Improving the Functionality Of Zifsmentioning
confidence: 99%
“…SALE has been reported to drastically affect both the stability and the adsorption properties of the resulting frameworks . For instance, the Sen group has recently investigated the SALE of ZIF‐8 and ZIF‐67 with 1,2,3‐triazole and found that after the SALE reaction, the 2‐methylimidazole ligand was completely substituted with 1,2,3‐triazole, which resulted in the transformation of the topological transformation of the parent framework from an SOD network to a diamond (DIA) network . The resulting MOFs, Co‐triazolate (MET‐4) and Zn‐triazolate (MET‐6) were stable up to 250 °C, but they were less thermally stable than the parent ZIF‐67 and ZIF‐8, respectively.…”
Section: Strategies For Improving the Functionality Of Zifsmentioning
confidence: 99%
“…MOFs materials have many advantages (large specific surface area, diversity of structure, adjustable pore size, unsaturated metal position and modifiable frameworks) and are used in many fields (gas storage and separation, optical materials, magnetic materials, catalytic materials, sensing material and biological materials) [4][5][6][7]. ZIF-8 has attracted extensive research interest because of its simple synthesis and various formulations, easy modification, and its potential applications in catalysis and gas separation [8][9][10]. Several researchers have reported the reason why ZIF-8 has high CO 2 adsorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…e thermal stability, CO 2 adsorption properties, and excellent selectivity are also important performance parameters for the practical application of ZIF-8 materials. e thermal stability of the reported MOF materials is mostly around 400°C and less than 500°C [11][12][13][14]. erefore, the thermal stability and CO 2 selectivity and adsorption properties of ZIF-8 materials should be further improved, expanding new application fields to meet the needs of the metallurgical industry and thermal power industry.…”
Section: Introductionmentioning
confidence: 99%